2023
DOI: 10.7189/jogh.13.06001
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of COVID-19 vaccination: A systematic review

Abstract: Background Safe and effective vaccination is considered to be the most critical strategy to fight coronavirus disease 2019 (COVID-19), leading to individual and herd immunity protection. We aimed to systematically review the economic evaluation of COVID-19 vaccination globally. Methods We performed a systematic search to identify relevant studies in two major databases (MEDLINE/PubMed and EBSCO) published until September 8, 2022. After deduplication, two researchers ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…A vast array of clinical studies have confirmed that COVID-19 vaccines are highly effective, even more so than those used for influenza vaccination (i.e., 80–90% vs. 50–60% efficacy against laboratory-confirmed symptomatic infections) [ 5 ], and relatively safe, since the burden of serous side-effects is orders of magnitude lower than the organic injuries caused by COVID-19 [ 6 ]. Besides the clinically favorable balance between efficacy and side effects, a recent systematic literature review also concluded that universal administration of COVID-19 vaccine is a cost-effective and cost-saving strategy for attenuating viral spread and averting the many adverse clinical consequences caused by COVID-19 illness [ 7 ]. Among the general population, older individuals are those more vulnerable to COVID-19 illness, in that the risk of unfavorable clinical progression, hospitalization, ICU admission and death is magnified compared to younger people [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A vast array of clinical studies have confirmed that COVID-19 vaccines are highly effective, even more so than those used for influenza vaccination (i.e., 80–90% vs. 50–60% efficacy against laboratory-confirmed symptomatic infections) [ 5 ], and relatively safe, since the burden of serous side-effects is orders of magnitude lower than the organic injuries caused by COVID-19 [ 6 ]. Besides the clinically favorable balance between efficacy and side effects, a recent systematic literature review also concluded that universal administration of COVID-19 vaccine is a cost-effective and cost-saving strategy for attenuating viral spread and averting the many adverse clinical consequences caused by COVID-19 illness [ 7 ]. Among the general population, older individuals are those more vulnerable to COVID-19 illness, in that the risk of unfavorable clinical progression, hospitalization, ICU admission and death is magnified compared to younger people [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews suggest that vaccination against a variety of diseases (i.e., pneumococcal disease, varicella, tuberculosis) is a cost-effective or cost-saving intervention [ 113 , 114 , 115 , 116 ]. Additionally, a recent systematic review showed that the COVID-19 vaccination program appears to be a cost-effective or cost-saving intervention [ 117 ]. Therefore, the implementation of effective vaccination programs worldwide is essential to save lives and resources, and improve quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Although vaccination promotes public health and it is a cost-effectiveness intervention even in case of COVID-19, 1315 vaccine hesitancy is still one of the biggest threats to global health 16 . Socio-demographic variables, psychological factors, vaccine hesitancy, COVID-19 related variables, personal beliefs, knowledge, fear, conspiracy theories, fake news, and trust are the most important factors that influence individuals’ decision to accept the COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 That is, the Heart Failure Association of the European Society of Cardiology and the American Heart Association suggest COVID-19 vaccination as soon as possible to individuals with heart failure, heart disease, heart attack, and cardiovascular risk factors since they are high risk groups to develop COVID-19 outcomes. 12 Although vaccination promotes public health and it is a cost-effectiveness intervention even in case of COVID-19, [13][14][15] vaccine hesitancy is still one of the biggest threats to global health 16 . Socio-demographic variables, psychological factors, vaccine hesitancy, COVID-19 related variables, personal beliefs, knowledge, fear, conspiracy theories, fake news, and trust are the most important factors that influence individuals' decision to accept the COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%